2017
DOI: 10.1186/s12931-016-0495-4
|View full text |Cite
|
Sign up to set email alerts
|

No convincing association between genetic markers and respiratory symptoms: results of a GWA study

Abstract: BackgroundRespiratory symptoms are associated with accelerated lung function decline, and increased hospitalization and mortality rates in the general population. Although several environmental risk factors for respiratory symptoms are known, knowledge on genetic risk factors is lacking. We aim to identify genetic variants associated with respiratory symptoms by genome-wide association (GWA) analyses.MethodsWe conducted the first GWA study on cough, dyspnea and phlegm among 7,976 participants in the LifeLines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Genome-wide association studies (GWASs) have highlighted pathways underlying a range of respiratory traits and diseases, and highlighted potentially relevant drug targets [ 12 , 13 ]. Previous GWASs of sputum production [ 14 17 ] have not identified any genome-wide significant findings.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWASs) have highlighted pathways underlying a range of respiratory traits and diseases, and highlighted potentially relevant drug targets [ 12 , 13 ]. Previous GWASs of sputum production [ 14 17 ] have not identified any genome-wide significant findings.…”
Section: Introductionmentioning
confidence: 99%
“…Among those differentiation expressed lncRNAs, several thoroughly studied molecules including A2MP1, C1QTNF1-AS1, CASC2, FTCDNL1, FTX, LOC339975 and TWIST1, which expressed in other diseases, were also significantly changed in LHBT. 50 SNPs were identified and evaluated for replication by Zeng et al Through genome-wide association analysis, Rs16918212 located in A2MP1 was associated with cough in both the identification odds ratio and the meta-analyzed replication cohort [ 32 ]. Li et al showed that C1QTNF1-AS1, who firstly down-regulated miR-221-3p and then up-regulated SOCS3, can inhibit the proliferation, migration and invasion of human liver cancer cells, and further accelerate apoptosis by acting on the JAK/STAT signaling pathway [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…We sought replication in five general population cohorts which surveyed participants for chronic sputum production; Generation Scotland [25], EXCEED Study [26], LifeLines 1, LifeLines 2 and Vlagtwedde-Vlaardingen [17]. Further details are provided in the Supplementary text.…”
Section: Replicationmentioning
confidence: 99%
“…Genome-wide association studies have highlighted pathways underlying a range of respiratory traits and diseases, and highlighted potentially relevant drug targets [16, 17]. Previous genome wide association studies of sputum production have been limited to cohorts of smokers [18, 19] or those with diagnosed COPD [20, 21] and have not identified any genome-wide significant findings.…”
Section: Introductionmentioning
confidence: 99%